Cost-effectiveness of GRAZAX ® for prevention of grass pollen induced rhinoconjunctivitis in Southern Europe - Canonica, G.W.; Poulsen, P.B.; Vestenbæk, U. (Respiratory medicine, 2007)
Allergic rhinoconjunctivitis is a global health problem. Around 14 million people in Spain, France, Italy, and Austria suffer from grass pollen induced allergic rhinitis. Standard care only provides symptoms relief, while allergen specific immunotherapy (SIT) treats the underlying cause of the disease. Grazax ® from ALK-Abelló is a new, tablet-based, effective route of SIT for home treatment. The objective was to assess the cost-effectiveness of Grazax ® in four Southern European countries. A prospective pharmacoeconomic analyses was carried out alongside a multinational, clinical trial measuring the efficacy of Grazax ®. Pooled data on resource use and health outcomes were collected. A societal perspective was adopted, and the analysis had a nine-year time horizon. The primary outcome measure was quality adjusted life years (QALYs). Grazax ® was superior to standard care for all efficacy endpoints, including QALYs gained, and resulted in significantly less use of rescue medication and fewer hours missed from work. Grazax ® was cost-effective for all countries for an annual price in the range of €1500–€1900. The result was improved by inclusion of future costs of asthma and exclusion of Spanish trial centers which experienced an exceptionally low pollen season. The analysis illustrates that allergen SIT with Grazax ® for grass pollen induced rhinoconjunctivitis is a cost-effective intervention in Southern Europe.